A taxonomic review of Walteriella Kazantsev, 2001 (Coleoptera: Cantharidae) from Taiwan, with description of a new species and a nomenclatural act on Leiothorax Wittmer, 1978 - Hsiao, Yun; Okushima, Yûichi (Zootaxa, 2025)
The genus Walteriella Kazantsev, 2001 is a small group of Asian soldier beetles distributed across South Asia, mainland Southeast Asia and southern East Asia. In the present study, the Taiwanese fauna of Walteriella is reviewed and four species are recognised: W. brunnea (Wittmer, 1955), W. sanguinea brevemarginata (Wittmer, 1983), W. taiwana (Kasantsev, 1999) and W. kasugana sp. nov. The description of the new species and the diagnoses of the named species are supplemented with illustrations of the habitus and diagnostic characters, a distribution map, phenological data and an identification key to species of Walteriella in Taiwan. Furthermore, we compare Walteriella with two similar genera, Leiothorax Wittmer, 1978 and Stenothemus Bourgeois, 1907 and discuss the generic status of Walteriella. Leiothorax Wittmer was found to be a junior homonym of Leiothorax Pinna, 1974 (Malacostraca: Decapoda: Caridea) and is hereby replaced by Neoleiothorax nom. nov. The species originally included in the genus are transferred as follows: N. kashmirensis (Wittmer, 1978) comb. nov., N. kopetzi (Švihla, 2004) comb. nov., N. minutus (Wittmer, 1974) comb. nov. and N. pseudominutus (Kopetz, 2008) comb. nov.